여재순환형 여과장치에서 여재에 따른 오염물질의 처리 - 고연실(Yeon Sil Go); 서영교(Young Gyo Seo); 이풀잎(Pul Eip Lee); 황유훈(Yu Hoon Hwang); 김범수(Bum Su Kim); 이태진(Tae Jin Lee) (Daehan hwan'gyeong gonghag hoeji, 2019)
장치 내부에서 여재가 순환하는 특성을 가진 여과장치를 이용하여 SS, T-P, CODmn 그리고 T-N의 제거율을 살펴보았다. 여재 부피대비 20%의 순환량을 가질 때 SS, T-P, CODmn 그리고 T-N 제거율은 각각 90%, 74%, 89% 그리고 15%로 처리효율이 가장 뛰어났다. 여재의 표면거칠기를 높게 하여 처리하였을 때 SS의 경우 반응속도상수는 0.024 h-1에서 0.042 h-1로 나타나 기존 여재보다 약 75%의 처리 속도 개선효과가 있었으나 CODmn, T-N 또는 T-P의 경우 그 효과는 미미하였다. 철 분말입자를 여재 표면에 부착하여 여과장치를 운전하였을 때 T-P의 경우 제거 개선효과가 두드러지게 나타났으며, 초기 5.80 mg/L 질산성 질소의 약 83%가 암모니아성 질소로 전환되었다. The removal efficiencies of SS, T-P, CODmn and T-N were examined using a filtration unit with the circulation of the suspended media. The removal efficiencies of SS, T-P, CODmn and T-N were 90%, 74%, 89% and 15%, respectively, when the circulation rate of the media was 20% of the total media volume. When the surface roughness of the media was increased, the reaction rate constant was 0.024 h-1 to 0.042 h-1 in the case of SS, which was 75% faster than the media without increment of roughness. In the case of CODmn, T-N or T-P, the removal efficiencies were negligible with the regardless of roughness. When iron powder particles were attached to the surface of the filter media, the removal rate of T-P was remarkably improved and about 83% of the initial 5.80 mg/L nitrate was converted to ammonia-nitrogen. KCI Citation Count: 0